Magnetic Resonance Cholangiopancreatography (MRCP) for Suspected Bilio-Pancreatic Disease: Should the Endoscopist Take a Second Look? - Wehrmann, T.; Eckardt, A. J.; Riphaus, A. (Zeitschrift für Gastroenterologie, 2013)
Introduction: MRCP enables a planar ductography of the pancreatobiliary system, which for diagnostic purposes may render ERCP unnecessary. However, the interpretation of MRCP findings is primarily performed by radiologists, and it is unclear whether additional interpretation of the MRCP results by the endoscopist alters clinical management.Patients and Methods: One-hundred and fifty-five consecutive patients, who were referred for further endoscopic procedures (EUS/ERCP) based on MRCP findings (performed within 4 weeks prior to admittance; a written radiological report as well as the digital images were available) were enrolled. Before the endoscopic examinations were done, the MRCP images were re-evaluated by an experienced endoscopist who was in charge of the further endoscopic management. The interpretations of the MRCP images by the radiologist and the endoscopist were then compared with the final diagnosis after the further endoscopic evaluation. Additionally, the recommendations made by the endoscopist for further patient management before and after MRCP image analysis were evaluated.Results: The MRCP image quality was judged sufficient by the endoscopist in the majority of the cases (80 %).The diagnostic accuracy of the MRCP findings was 73 % based on the interpretation by the radiologist and 86 % from the interpretation of the endoscopist. In 14 patients the endoscopist scheduled an EUS instead of an ERCP after he had viewed the MRCP images. Overall, the endoscopic work-flow was modified by the additional interpretation of the MRCP by the endoscopist in 25/155 (16 %) of the cases.Limitations: This is a non-randomized, unblinded single-observer assessment.Conclusion: MRCP images should be additionally interpreted by an endoscopist before further endoscopic procedures are scheduled.
Keywords: MRCP; ERCP; EUS